On the robustness of entanglement in analogue gravity systems - Bruschi, David Edward; Friis, Nicolai; Fuentes, Ivette; Weinfurtner, Silke (IOP Publishing, 2013)
We investigate the possibility of generating quantum-correlated quasi-particles utilizing analogue gravity systems. The quantumness of these correlations is a key aspect of analogue gravity effects and their presence allows for a clear separation between classical and quantum analogue gravity effects. However, experiments in analogue systems, such as Bose–Einstein condensates (BECs) and shallow water waves, are always conducted at non-ideal conditions, in particular, one is dealing with dispersive media at non-zero temperatures. We analyse the influence of the initial temperature on the entanglement generation in analogue gravity phenomena. We lay out all the necessary steps to calculate the entanglement generated between quasi-particle modes and we analytically derive an upper bound on the maximal temperature at which given modes can still be entangled. We further investigate a mechanism to enhance the quantum correlations. As a particular example, we analyse the robustness of the entanglement creation against thermal noise in a sudden quench of an ideally homogeneous BEC, taking into account the super-sonic dispersion relations.